Socioeconomic impact of forests: Pilots outcome in rural Peru - Reyes, Teija (2018)
With a better knowledge of the real life of forest communities, it is possible to improve the ecological, social and economic sustainability of rural communities. Forestry socioeconomic monitoring evaluates the realities in which rural communities live. One tool for this is national household surveys on the impacts of forests on living standards. This provides accurate estimates on the value of forests, and living conditions in rural areas. Regular measurements and standards allow capturing the true value of forests and their contribution to the well-being and income of households. This article evaluates the development of the methodology, tools and collection of forest socioeconomic data in six pilots adapted to the Peruvian reality, which were part of the National Forest Inventory Program in Peru carried out by the United Nations Food and Agriculture Organization. Agriculture (FAO) in collaboration with the Ministry of the Environment and the Ministry of Agriculture. Good forest monitoring improves the reputation and gives greater visibility to the forestry sector in relation to other entities responsible for policy formulation.